2015
DOI: 10.1089/jmf.2014.3251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Red Ginseng Extract Enriched in Ginsenoside Rg3 on the Differentiation and Mineralization of Preosteoblastic MC3T3-E1 Cells

Abstract: In this study, red ginseng extract (RGE) was converted into high-content minor ginsenosides by fermenting with Bgp1 enzymes at 37°C for 5 days. Compared to the RGE, the minor ginsenoside contents were increased in fermented red ginseng extract (FRGE). Moreover, the amount of minor ginsenosides such as Rh1 (11%) and Rg2 (16%) was slightly augmented, while the level of Rg3 (33%) was significantly increased after bioconversion. Furthermore, we also examined and compared the effect of RGE and FRGE on the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…We proved that the up‐regulated expression of RUNX2 was suppressed by Rb1 both in vivo and in vitro, indicating that Rb1 inhibited VSMC phenotype switching of VC. Interestingly, it was demonstrated that ginsenosides promote osteogenic differentiation . Ginsenoside Rg1 promotes rat bone marrow mesenchymal stem cell (rBMSC) osteogenic differentiation by activating the GR/BMP‐2 signalling pathway .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We proved that the up‐regulated expression of RUNX2 was suppressed by Rb1 both in vivo and in vitro, indicating that Rb1 inhibited VSMC phenotype switching of VC. Interestingly, it was demonstrated that ginsenosides promote osteogenic differentiation . Ginsenoside Rg1 promotes rat bone marrow mesenchymal stem cell (rBMSC) osteogenic differentiation by activating the GR/BMP‐2 signalling pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg1 promotes rat bone marrow mesenchymal stem cell (rBMSC) osteogenic differentiation by activating the GR/BMP‐2 signalling pathway . Moreover, ginsenosides Rg3, Rd and Rh2(S) were reported to induce the differentiation and mineralization of MC3T3‐E1 cells . Nevertheless, none of the studies above investigated the effect of Rb1 on VSMC phenotype switching or the role of the PPAR‐γ/β‐catenin pathway in VC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were washed by PBS buffer and then suspended in Tris/HClbuffer (10 mM, pH 7.5) supplemented with 0.1% Triton X-100, 2 mM MgSO4 and incubated for 2 hat 37°C. Absorbance was taken at 405 nm and ALP activity was measured using p-Nitrophenol phosphate as a substrate (Siddiqi et al, 2015).…”
Section: Alkaline Phosphatase (Alp) Activitymentioning
confidence: 99%